Remnants of the Dutch Infrastructure in Banda Aceh During the Independence Revolution - Muhjam Kamza; Farhan Fadillah; M Yusrizal (IHiS (Indonesian Historical Studies), 2022)
The feud between the Dutch and Indonesia again peaked after Indonesiaproclaimed independence on August 17, 1945. War broke out in almost everyregion in Indonesia, Aceh was one of them. The basis of the hatred of the Acehnesetowards the Dutch which grew under the spirit of jihad fisabilillah [war in the wayof Allah] made the Veranda of Mecca was never negligent in opposing the Dutchcompany. Uniquely, the prolonged war that erupted in Aceh did not affect theDutch heritage buildings in Banda Aceh as the epicenter of the resistance. Thisstudy examines the function of the infrastructure of the Dutch colonial remains inBanda Aceh during the Indonesian Independence Revolution. The historicalresearch method is emphasized on utilizing primary sources in the form essayscompiled by historical actors and witnesses who lived during the independencerevolution, as well as Dutch documents in the form of photographs and maps.According to the result, the Dutch heritage infrastructure in Banda Aceh duringthe independence revolution did not find any damage caused by war and wasused for various revolutionary purposes. These buildings are generally used asthe initial function and some of them are used according to the revolutionary war.However, the practice of vandalism in the form of crossing out and pastinginformation dissemination stickers often took place in the buildings at that time.